Kriteria Pasangan Hidup dalam Perkawinan Menurut Ajaran Islam untuk Dapat Mewujudkan Keluarga Sakinah Mawadah Warahmah - Sunari Sunari; Ratih Dwi Pangestu; Dedy Muharman (Syntax Corporation, 2023)
In this study the author uses literature research with secondary data sourced from three legal materials in the form of primary legal materials, including the Compilation of Islamic Law, translation of the Quran and Hadith. Secondary legal materials, namely books of jurisprudence or opinions of scholars / schools of thought about and literature that has relevance to the discussion while tertiary legal materials, including dictionaries, encyclopedias, and so on. In conclusion, Marriage in the teachings of Islam is worship so that its implementation must meet the requirements and pillars that have been set. In addition, in order for this marriage to run long and can achieve its goals, namely a family that is sakinah, mawadah and warahma, then in Islamic teachings it is also determined or hinted who is appropriate or ideal to choose, because Islam wants the marriage to run until the end of life.